Herbario Virtual. - Guerra Barreros, Danny Luis (2018)
The present research project is based on the use of technology to create a VIRTUAL HERBARY of the Technical University of Cotopaxi, which is available on the website of the institution, thus allowing free access to people interested in visiting and gain knowledge of the botanical species collected in the province with their respective location, classification, common and scientific name, description, usefulness, among other parameters contemplated for the presentation of the species. The project consists of three stages that are: 1. Generating a database of samples collected in the herbarium of the Technical University of Cotopaxi. (Responsible Ciencias Agropecuarias y Recursos Naturales Faculty - Agronomic Engineering) 2. Designing a virtual tour of the herbarium of the Universidad Técnica de Cotopaxi from the database generated. ( Responsible Ciencias Humanas y Educación Faculty – Bachelor in Graphic Design) 3. Designing of an application for the identification of plants from the physical repository of the herbarium of the Universidad Técnica de Cotopaxi. (Responsible Ciencias de la Ingenieria y Aplicadas Faculty - Systems Engineering) This research work fulfilled the first stage enunciated, which allowed us to save, collect, systematize the information obtained from a process of identification of the samples collected in the herbarium of the university through; sample assembly, field label, initial and final taxonomic revision. The status of each collection was examined, discarding the inconsistencies in classification, labeling and those that were incomplete due to damage to its leaves, stems or fruits; Subsequently, the samples were cured. The study was based on descriptive research, characterizing the characteristics and differences between the different plant species of the herbarium, as well as applied research, interweaving the theoretical knowledge with the practical, so that the material and access to society; The techniques used were direct observation and documentary review. The product obtained is the database in an Excel sheet and the generation of biosafety protocols.